Humor at work that works: A multi-level examination of when and why leader humor promotes employee creativity - Zhang, Yajun; Yin, Changqin; Akhtar, Muhammad Naseer; Wang, Yongqi (Frontiers in Psychology, 2022)
Although the role of leadership in fostering employee creativity has been extensively studied, it is still unclear whether and how leader humor affects employee creativity. Drawing upon cultural representation theory (CRT), we examined creative self-efficacy as a mediator and traditionality as a situational factor in the relationship between leader humor and employee creativity by analyzing a sample of 306 employees and 88 leaders (paired data) collected through survey questionnaire from firms based in Hubei Province, China, covering the industries of automobile, IT, and medicine. Following the multi-level examination, leader humor was positively related to employee creativity, and creative self-efficacy was found to mediate the impact of leader humor on employee creativity. Furthermore, traditionality moderated the effect of leader humor on creative self-efficacy, as well as the indirect effect of leader humor on employee creativity through creative self-efficacy. This study provides a social psychological explanation for the association between humor and employee creativity, deepens the current understanding of the influence process of leader humor. Finally, the theoretical and practical implications of the study are discussed at the end alongside limitations and recommendations for future research.